Localization of Window Air Conditioner Inverter Model from Thailand - Sarkar, Susthanu (My University, 2022)
The objective of this industrial training is to learn something about industries practically and to be acquainted with the working type of a technical worker to get simply consistent with industrial environment. In this project work the layout of LG Procurement Management and Localization of Window RAC Development has been studied, right from Raw Material details to production line to final dispatch line. The details of LG Purchasing Management, Costing, Cost Reduction Management, Value Innovation (VI) activity have been studied thoroughly throughout this thesis. The development of WRAC from Thailand is discussed briefly and the major role of Purchasing Department in LG is briefly elaborated with various aspects. Detailed study of Procurement Management, Cost Analysis and Complete Development Process has been described.
Keywords: Localization, Cost Reduction Management, VI Activity, Window Residential Air Conditioner, FPA Process, New Part Development.